ANALISIS BALANCED SCORECARD SEBAGAI ALAT PENGUKURAN KINERJA PADA CV YAMAHA SINAR UTAMA HIDAYATULLAH SAMARINDA - Kamalia Pantalisa; Cornelius Rantelangi; Anisa Kumawardani (AKUNTABEL, 2015)
This research determine: How the performance of CV Yamaha Sinar Utama Hidayatullah Samarinda during 2012 and 2013 measured using the Balanced Scorecard concept. And  the research pupose   is to determine the performance of CV Yamaha Sinar Utama Hidayatullah Samarinda in 2012 and 2013 seen from the Balanced Scorecard concept. Based on the results of the research indicate: (1) Financial Perspective of CV Yamaha Sinar Utama in 2012 is quite good, while in 2013 is still not good. In 2013 the company was not able to optimize the use of assets to generate the level of sales and higher investment returns. Similarly, the percentage of sales growth in 2013 were lower than the previous year. ROI and profit margin percentage is still low. (2) Customer Perspective of CV Yamaha Sinar Utama in 2012 and 2013 is quite good. Customer Rettention percentage is fairly high, although the percentage of Customer Acquisition had decreased. (3) Internal Business Process Perspective of CV Yamaha Sinar Utama in 2012 and 2013 is quite good, because every year the company is always able to provide the addition of new products. (4) Learning and Growth Perspective of CV Yamaha Sinar Utama in 2012 and 2013 is quite good, it is seen from the increasing percentage of employee training and employee productivity is high enough and the number of employees out every year si become less. Keyword: Balanced Scorecard, Financial Perspective, Customer Perspective, Internal Business Processes Perspective, Learning and Growth Perspective